The Wiley-Blackwell handbook of legal and ethical aspects of sex offender treatment and management - Harrison, Karen, 1974-; Rainey, Bernadette (Malden, MA : Wiley-Blackwell, 2013)
This handbook combines the latest theory on a high-profile, complex subject in criminology, exploring the legal and ethical dimensions of society's response to sex offenders in jurisdictions from the USA to Japan. The first publication to offer a detailed and wide-ranging analysis of legal and ethical issues relating to sex offender treatment and managementCovers a range of related issues, from media coverage to equality dutiesPresents research from numerous national jurisdictions including the UK, USA, Australia, New Zealand, Canada, Norway, Germany, Netherlan.
Sexual offenders, law, and morals : can behaviour and attitudes be changed by legal and moral efforts? / Knut Hermstad -- Human rights and sexual offenders / Bernadette Rainey -- Sex offenders, consent to treatment, and the politics of risk / Phil Fennell -- Special offender groups and equality : a duty to treat differently? / Bernadette Rainey -- Expert evidence, ethics, and the law / Tony Ward -- Ethical issues in sex offender research / Tony Ward and Gwenda Willis -- Reintegrative and disintegrative shaming : legal and ethical issues / Anne-Marie McAlinden -- Castrate 'em? : treatments, cures, and ethical considerations in UK press coverage of chemical castration / Peter Brown -- Sentencing sex offenders : an international comparison of sentencing policy and legislation / Karen Harrison -- Sentencing and criminal justice policy for sexual crimes in Japan : possible impact of the lay judge system / Mari Hirayama -- Unique disadvantages, unique needs : Native American sex offenders / Nora V. Demleitner -- Mandated reporting laws : experiences from Israel / Sheri Oz -- Treatment for adult sex offenders : may we reject the null hypothesis? / Marnie E. Rice and Grant T. Harris -- Ethical issues in treating sexual offenders : applying empirically-based process features of treatment delivery / W.L. Marshall and L.E. Marshall -- A forensic psychologist's involvement in working with sex offenders / Daniel T. Wilcox -- Punishment and the rehabilitation of sex offenders : an ethical maelstrom / Tony Ward and Chelsea Rose -- Distinguishing moral and clinical decisions in sex offender programmes : the good lives model and virtue ethics / Bill Glaser -- Pharmacological treatment of sexual offenders and its legal and ethical aspects / Raphaela Basdekis-Jozsa, Daniel Turner, and Peer Briken -- Female sexual offenders : the need for a gender responsive approach / Sherry Ashfield, Sheila Brotherston, Hilary Eldridge and Ian Elliott -- A convergent approach to sex offender risk assessment / Jeffrey C. Singer, Douglas P. Boer, and Martin Rettenberger -- Sex offender registration in the USA and the UK : emerging legal and ethical debates / Terry Thomas -- A more ethical way of working : circles of support and accountability / Stephen Hanvey and Mechtild H'ing -- Ethical practice and the use of the polygraph in working with sex offenders / Daniel T. Wilcox -- Sex offender civil commitment : legal and ethical issues / Rebecca L. Jackson and Christmas N. Covell -- Sex offender residence restrictions : a systematic review of the literature / Daniel Pacheco and J.C. Barnes -- The travelling sex offender : monitoring movements across international borders / Terry Thomas -- Hell is other people : the importance of controlling paedophilic activity / Xanth Mallett and Jann Karp.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Sex offenders; Sex offenders -- Rehabilitation; Sex offenders -- Treatment; Sex crimes -- Treatment; Sex crimes -- Moral and ethical aspects; Forensic psychology; Forensic psychology; Sex crimes -- Moral and ethical aspects; Sex crimes -- Treatment; Sex offenders; Sex offenders -- Rehabilitation; Sex offenders -- Treatment; SOCIAL SCIENCE -- Criminology; Electronic books; Electronic books